(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article considers the prospects for the development of the educational process, analyzes the optimal shells of distance learning (DL) , including a complex of distance technologies used both in full-time education as an auxiliary tool. The main vector of modernization of education is the development and implementation of an effective mechanism of the open education system. The need for open education is also explained by the accelerating process of obsolescence of knowledge and the requirements of modern development of civil society. However, many issues of the development of the open education system remain not fully developed and poorly researched. The solution of these issues is just one of the main tasks of this study. The purpose of the article: to study the direction of education in the process of its development: the fundamentalization of education through the integration of science and education; the interdisciplinarity of education; the permanence of the education process on the basis of self-development; the creative nature of learning; informatization of education; increasing the level of educational potential of the education system.